Challenge of the Super Friends. Attack of the legion of doom [videorecording (DVD)] - Jarwich, Don; Patterson, Ray; Urbano, Carl; Cassidy, Ted; Kasem, Casey; Messick, Don; Welker, Frank; Hastings, Bob; Chartoff, Melanie; Angel, Jack; Holt, Bob; Aradal, Ed; et al. (Challenge of the super friends (Television program), 2003)
A nostalgic compilation of the classic 1978 TV cartoons. Superman leads a team comprised of the greatest DC Comics superheroes against a team of 13 of the most notorious super villains.